Chemical composition of rocks and minerals from the Central Atlantic fracture zones - Yury M Pushcharovsky; Alexander A Peyve; Yury N Raznitsin; Elena S Bazilevskaya (PANGAEA, 1995)
The monograph summarizes materials on geology and deep structure of the Central Atlantic fracture zones. These materials have been obtained during eight expeditions of R/V extquotesingle extquotesingleAkademik Nikolaj Strakhov extquotesingle extquotesingle. The studies have been based on the integrated geological approach. As a result, many new tectonic, magmatic, metallogenic and historical-geological features of these phenomenal structures of the deep ocean have been revealed.
Supplement to: Pushcharovsky, YM et al. (1995): The Central Atlantic Fracture Zones. Geological Institute of the Russian Academy of Sciences, Transactions, vol. 495. Moscow, GEOS Publ. (S.D. Sokolov, Ed.), 164 pp